IMPACT OF THE TYPE OF DELIVERY ON GROWTH, BODY COMPOSITION AND MOTOR PERFORMANCE OF CHILDREN AND YOUNG PEOPLE (Arquivos do Mudi, 2023)
The aim of this study was to investigate the impact of cesarean delivery (CD) and normaldelivery (ND) on growth, body composition and motor performance of children and youngpeople. The study included 114 children and young people (11 to 18 years old) who weredivided into two groups (ND and CD). Participants underwent a battery of anthropometricmeasurements and motor tests. Children and young people born with CD showed greaterperformance in the trunk elevation test in extension (flexibility), shorter distance covered (m)in the treadmill test (aerobic resistance), greater amount of subcutaneous tissue andendomorphy component than children and young people born from ND. It was observed thatchildren born with CD in this study had a greater amount of body fat, greater trunk flexibilityand shorter distance covered on a treadmill, suggesting important advantages for childrenborn with ND in relation to obesity and aerobic capacity. These components of physicalfitness related to health are determinant for the development of chronic degenerative diseases.This study reveals that ND should also be encouraged as a health promotion strategy.